HOW LISTENING DEEMED AS THE MOST DIFFICULT ENGLISH SKILLS DURING ONLINE LEARNING AMONG STUDENTS? - Triastama Wiraatmaja; Lovie Kartika Sari; Pramujiono Cahyadi (Universitas Muhammadiyah Metro, 2022)
Despite the growing interest in online learning over the past years, Indonesian students had to adjust to online interactions. Thus, Indonesian students, in general, still needed to be thoroughly instilled in this learning mode due to various challenges. This qualitative research aimed to discover the most difficult English skills during online learning from Indonesian students’ perspectives. This research utilized a survey design to rank the complex English skills; Writing, Speaking, Listening, and Reading. There were 55 students from different majors as participants from various universities in Indonesia who already partake in English courses by undergoing online mode. The instruments in this research are questionnaires regarding how one of the English skills is regarded as the most difficult during online learning, including the cause and methods to lessen the difficulty of obtaining thorough explanations. Critical Discourse Analysis was utilized as a data analysis technique to comprehend multiple perspectives better; in educational and non-educational contexts. The findings discovered that the majority of the participants deemed listening as the most difficult one. This research also discovered the factors that made listening difficult among students and the methods devised to lessen the difficulties in listening during online learning.